2013
DOI: 10.1364/oe.21.024819
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cellular objects through diffraction images acquired by flow cytometry

Abstract: It was found that the diffraction images acquired along the side scattering directions with objects in a cell sample contain pattern variations at both the global and local scales. We show here that the global pattern variation is associated with the categorical size and morphological heterogeneity of the imaged objects. An automated image processing method has been developed to separate the acquired diffraction images into three types of global patterns. Combined with previously developed method for quantifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
(41 reference statements)
2
35
0
Order By: Relevance
“…5 show a trend with the speckles appearing larger for cells with increasing t p . The visual differences are consistent with the facts that apoptotic cells tend to have fragmented nuclei of reduced volumes which lead to larger speckles [25]. Despite the fact that the mean values of s-CLS increases with t p as shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…5 show a trend with the speckles appearing larger for cells with increasing t p . The visual differences are consistent with the facts that apoptotic cells tend to have fragmented nuclei of reduced volumes which lead to larger speckles [25]. Despite the fact that the mean values of s-CLS increases with t p as shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, it can be readily observed that apoptotic cells distribute differentially from the viable cells in a scatter plot of the angularly integrated side scatters (SSC) versus the forward scatters (FSC) obtained with the FCM assay [18,19]. These results suggest some strong correlations between the morphological variations in apoptotic cells relative to the viable cells and spatial distribution of scattered light, which are consistent with the experimental and modeling studies on light scattering by biological cells of different morphology in general [15][16][17][20][21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is especially true in the case of diffraction imaging to record spatial distribution of coherent light scattered by single cells with a flow cytometer. Previous studies by different groups, including ours, have developed simplified OCMs of constant or varying RI within a cell and/or its individual organelles built by spheres or spheroids [4,37,38], mathematical surfaces [39], reconstruction from confocal image stack data for nucleus only [10,33,40] or Gaussian random sphere models for nucleus and mitochondria [41,42]. These models may be sufficiently accurate for investigation of certain aspects of scattered light distributions such as angularly (1D) or spectroscopically resolved measurements [43].…”
Section: Discussionmentioning
confidence: 99%